Broad vaccine protection against Neisseria meningitidis using factor H binding protein. Issue 49 (17th November 2020) - Findlow, Jamie; Bayliss, Christopher D.; Beernink, Peter T.; Borrow, Ray; Liberator, Paul; Balmer, Paul
Highlights: MenB vaccines with FHbp variants can be highly immunogenic against diverse strains. Lipidated FHbp induces superior immune responses compared with nonlipidated FHbp. MenB vaccines differ in presentation and number of FHbp antigens included. Lipidated FHbps from both subfamilies A and B successfully provide broad protection. The critical role of FHbp limits the risk of vaccine escape and strain replacement. Abstract: Neisseria meningitidis, the causative agent of invasive meningococcal disease (IMD), is classified into different serogroups defined by their polysaccharide capsules. Meningococcal serogroups A, B, C, W, and Y are responsible for most IMD cases, with serogroup B (MenB) causing a substantial percentage of IMD cases in many regions. Vaccines using capsular polysaccharides conjugated to carrier proteins have been successfully developed for serogroups A, C, W, and Y. However, because the MenB capsular polysaccharide is poorly immunogenic, MenB vaccine development has focused on alternative antigens. The 2 currently available MenB vaccines (MenB-4C and MenB-FHbp) both include factor H binding protein (FHbp), a surface-exposed protein harboured by nearly all meningococcal isolates that is important for survival of the bacteria in human blood. MenB-4C contains a nonlipidated FHbp from subfamily B in addition to other antigens, including Neisserial Heparin Binding Antigen, Neisserial adhesin A, and outer membrane vesicles, whereas MenB-FHbp contains a lipidated FHbp from each subfamily (A and B). FHbp is highly immunogenic and a main target of bactericidal activity of antibodies elicited by both licensed MenB vaccines. FHbp is also an important vaccine component, in contrast to some other meningococcal antigens that may have limited cross-protection across strains, as FHbp-specific antibodies can provide broad cross-protection within each subfamily. Limited cross-protection between subfamilies necessitates the inclusion of FHbp variants from both subfamilies to achieve broad FHbp-based vaccine coverage. Additionally, immune responses to the lipidated form of FHbp have a superior cross-reactive profile to those elicited by the nonlipidated form. Taken together, the inclusion of lipidated FHbp variants from both FHbp subfamilies is expected to provide broad protection against the diverse disease-causing meningococcal strains expressing a wide range of FHbp sequence variants. This review describes the development of vaccines for MenB disease prevention, with a focus on the FHbp antigen.